A Study on the factors of river sustainability at Sungai Klang, Selangor / Muhammad Anuar Md Kassim - Md Kassim, Muhammad Anuar (2020)
River pollution is often the news in the newspapers in Malaysia. The problem of river pollution is often a problem that often occurs in this country. There are various causes that occur that cause river pollution to occur frequently. Sungai Klang is one of the rivers where river water pollution often occurs. There are various causes that cause pollution including among the dumping of garbage in the river, disposal of toxic waste and so on. Therefore, various parties need to play a role in curbing river pollution continues to occur. This purpose is to improve the environmental quality of river sustainability at Sungai Klang by focusing on three (3) objectives which is to understand the knowledge related to river sustainability from literature review, to identify the issues and factor of sustainability river at Sungai Klang and to recommend the solution that can improve the quality of river environment. This research was conducted with the data collection method through the quantitative method. Total of 48 online questionnaire survey was distributed using online platform. The final proposal is given using a conceptual framework that has three (3) elements which is economy, community and environment. These three (3) elements are elements taken from among the river sustainability factors that can be achieved.